2020
DOI: 10.28991/cej-2020-03091612
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Project Success in Residential Building Projects (RBPs) using Artificial Neural Networks (ANNs)

Abstract: Due to the urban population’s growth and increasing demand for the renewal of old houses, the successful completion of Residential Building Projects (RBPs) has great socioeconomic importance. This study aims to propose a framework to predict the success of RBPs in the construction phase. Therefore, a 3-step method was applied: (1) Identifying and ranking Critical Success Factors (CSFs) involving in RBPs using the Delphi method, (2) Identifying and selecting success criteria and defining the Project Success Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The main architectural design methods are explained in combination with architectural structure design principles in literature [18]. According to literature [19], deformation occurs during the construction and operation of engineering buildings due to the influence of many factors. If the deformation exceeds the prescribed limit, it will have an impact on the normal use of buildings, and in severe cases, it will jeopardize building safety and result in significant societal and human losses.…”
Section: Related Workmentioning
confidence: 99%
“…The main architectural design methods are explained in combination with architectural structure design principles in literature [18]. According to literature [19], deformation occurs during the construction and operation of engineering buildings due to the influence of many factors. If the deformation exceeds the prescribed limit, it will have an impact on the normal use of buildings, and in severe cases, it will jeopardize building safety and result in significant societal and human losses.…”
Section: Related Workmentioning
confidence: 99%
“…From this point of view, a distinction is made between ecological and economic sustainability. Studies have also found that realistic cost and time estimates are among the 10 most important success factors in residential building projects [13]. The need to develop infrastructure projects where one of the proofs is economic sustainability was the subject of another study [14].…”
Section: Introductionmentioning
confidence: 99%
“…ANNs have been used in various research fields, such as physics, medicine, geology, engineering, and specifically construction engineering [2][3][4][5]. In Tehran, ANNs are employed to predict the success of housing projects in the construction phase [6], Modified Neural Network Algorithm (MNNA) is used to optimize the gains of a controller, and a new mathematical modeling is introduced to promote the exploration form [7]. On the other hand, a NN predictive controller based on a genetic algorithm is designed for Automatic Voltage Regulator (AVR) [8].…”
Section: Introductionmentioning
confidence: 99%